THE PATTERNS OF APPLYING LEGAL THEORY IN THESIS WRITING OF STUDENTS OF ISLAMIC FAMILY LAW IN THE FACULTY OF SYARI’AH AND LAW AT UIN SUMATERA UTARA - Ibnu Radwan Siddik Turnip; Sukiati Sukiati; Irwan Irwan (Universitas Islam Negeri Mataram, 2022)
This study aims to see the pattern of application of legal theory in thesis writing of students of the Islamic Family Law Study Program (HKI) in the Faculty of Shari’ah and Law at UIN Sumatra Utara, to analyze the factors that influence the polarization of the application of legal theory in student thesis writing, and to explain solutions in overcoming uniformity and unpreparedness of students in using the theoretical framework and legal theory in writing a thesis. This research is qualitative research using content analysis. Data collection techniques were carried out using documentation methods, Focus Group Discussions (FGD), and interviews. The results indicate that there are six polarizations in the application of legal theory to a student thesis. First, the thesis does not use a theoretical framework that contains legal theories. Second, the thesis uses a theoretical framework but does not contain legal theories. Third, the thesis uses the theoretical framework and explains the legal theories that will be used as its analysis tool, but does not use it on analysis. Fourth, the thesis uses a theoretical framework and explains the legal theory in it, but the legal theory used as an analysis is different from the legal theory in the theoretical framework. Fifth, the thesis does not use legal theory in the theoretical framework, but the analysis uses legal theory. Sixth, a thesis that uses the theoretical framework and legal theory used in the theoretical framework then applies the legal theory in analyzing the results of his research. Factors that influence the polarization of the application of legal theory in student thesis writing are; factors of teaching materials and teaching lecturers, factors of supervisors, and factors of student seriousness. The proposed solutions in overcoming the non-uniformity and unpreparedness of students in using the theoretical framework and legal theory in thesis writing include; it is necessary to involve the Faculty and Study Program to take policies, uniformity of learning materials for Research Methodology courses, the role of the thesis supervisor and the role of students.